Centralized Voltage Regulation Algorithm in Distribution Networks containing Photovoltaic Generation - أحمد الحاج أحمد; تمام حيدر; رشا تقلا (Latakia University Journal -Engineering Sciences Series, 2023)
This paper presents a centralized voltage regulation algorithm in modern electrical networks containing photovoltaic generation (PV). Reference studies presented many decentralized voltage regulation algorithms, some of which are presented in this paper, where each inverter takes decisions separately depending on the value of the measured voltage on its output without taking into account the voltage of other nodes and even without a clear possibility of temporal coordination with other inverters, and this what makes the regulation process a randomly process. Most of these algorithms adapt the reactive power provided by the inverter, and then regulating the real power provided by the PV-system, when the demand for reactive power reached the physical limits of the Inverter. The application of the proposed algorithm in a test network showed advantages compared to a decentralized control algorithm that adopts the real and reactive power. The regulating process in the proposed algorithm is carried out in an orderly manner and according to the need, after investigating the state of voltage at all points, which reduces the number of Electronic switches on-off actions and thus extended their life. A communication network in the networks is the physical basis for Implementation of the proposed algorithm. The network modeling process was done in ETAP software and the regulation algorithm in MATLAB software.